A financial approach-based measurement of brand equity in the restaurant industry. Issue 7 (November 2017) - Choi, Serin; Choi, Kyuwan; Lee, Seoki; Lee, Kyuseok
Brand equity plays a significant role in the restaurant industry due to the competitive advantage gained by differentiation. It has been identified as a main component of intangible assets that decides the market value of a firm in the industry. Although the importance of brand equity has been well recognized in the restaurant literature, there has been little investigation regarding how to objectively quantify brand equity, especially by using secondary market data. Further, there is no publicly available brand equity data of restaurant firms thus far. For these reasons, this study aims to develop an approach on how to estimate a restaurant's brand equity not only by utilizing the secondary market data but also by incorporating the unique characteristics of restaurant firms. By proposing a restaurant-specific model to estimate brand equity, this study contributes to the restaurant literature and to the industry as a whole.